Development of the Teacher Candidates’ Level of being Affected from Public Personnel Selection Examination Scale - Fatma SUSAR KIRMIZI; Özge TARHAN (International Journal of Assessment Tools in Education)
This study aimed to develop a scale to evaluate teacher candidates' level of being affected from the public personnel selection examination. The participants of the study consisted of the final year students at Pamukkale University Education Faculty. The participants were 207 teacher candidates, of whom 143 were female and 64 were male. The validity and reliability study of the scale was conducted on the data gathered from teacher candidates studying at Art Teaching, Music Teaching, Turkish Language Teaching, Social Studies Education, Science Teaching, Psychological Counseling and Guidance Education, Elementary Education and Preschool Education departments of Pamukkale University Education Faculty. The Lawshe technique was used in the evaluation of the scale by experts. To determine the construct validity, factor analysis was performed on the data, and two sub-scales were identified. The factor loading values of the items in the first sub-scale ranged between 0,65 and 0,35, and those in the second sub-scale between 0,75 and 0,39. As a result of the analyses, the "Teacher Candidates' Level of Being Affected From Public Personnel Selection Examination Scale" (TCLBAPPSES) including 33 items, 23 negative and 10 positive, and two sub-scales was produced. The Cronbach's Alpha reliability coefficient was found as 0,86 for the first sub-dimension, 0,73 for the second sub-dimension, and 0,91 for the whole scale. As a result, it can be argued that the scale is reliable